Clinicopathological features of two cases of ETV6-NTRK3 rearranged papillary thyroid carcinoma: a case report - Ke, Jing; Cao, Minghua; Zhang, Wenzhong; Huang, Hua; Chen, Ping; Liu, Jinhua; Shan, Dan; Ke, Jie; Wang, Zerui; Liu, Junchen; Li, Yuan; Xiao, Sheng (Frontiers in Oncology, 2024)
Rearrangements involving the neurotrophic-tropomyosin receptor kinase (NTRK) gene family (NTRK1, NTRK2, and NTRK3) have been identified as drivers in a wide variety of human cancers. However, the association between NTRK rearranged thyroid carcinoma and clinicopathological characteristics has not yet been established. In our study, we conducted RNA NGS sequencing on paraffin section specimens from 106 patients with thyroid cancer retrospectively reviewed medical records of thyroid cancer patients and identified 2 cases with NTRK rearrangement, no additional molecular alterations were observed in either of these cases. The fusion of the rearrangement in both cases was ETV6(E4)::NTRK3(E14). By analyzing the clinicopathological features of these two cases, we found that both were characterized by multiple tumor nodules, invasive growth, and central lymph node metastases, indicating the follicular variant subtype of papillary thyroid carcinoma.Immunohistochemical staining profiles showed CD56-, CK19+, Galectin-3+, HBME1+. These clinicopathological features suggest the possibility of ETV6-NTRK3 rearranged thyroid carcinoma and highlight the importance of performing targeted RNA NGS sequencing gene fusion testing by FISH or NGS for these patients.